Relationship of Information Technology, Total Quality Management, Training, Reward, and Education on MSME Performance - Lusiana Lusiana; Silvia Sari (Yayasan Keluarga Guru Mandiri, 2025)
MSMEs are critical to economic growth but often face challenges that limit their performance. The research examines the influence of information technology, Total Quality Management (TQM), training, rewards, and level of education on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Padang. The research population comprised all MSME business actors in Padang, totaling 42,452 business units. The number of samples was determined using the Slovin formula; therefore, the number of samples in this study was 397 units. Data collection was carried out by distributing questionnaires. Data analysis will be performed using Structural Equation Modeling (SEM) with Smart-PLS software. The research results show that information technology, training, and education levels positively and significantly influence the MSME's performance. However, TQM and reward do not have a significant influence on MSMEs in Padang. This research recommends that MSMEs utilize and use information technology in their operations. Then, MSME business people must include employees in functional training and select employees with a higher level of education. This research contributes to understanding how Information Technology, Total Quality Management, Training, Reward, and Education collectively impact MSMEs' performance, providing valuable insights for improving their operational efficiency and growth.